2011
DOI: 10.1002/ange.201100956
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Branched‐Selective Alkyne Hydroacylation: A Ligand‐Controlled Regioselectivity Switch

Abstract: Alles eine Frage des Liganden: Durch die Wahl des geeigneten Diphosphanliganden kann eine vormals linear(l)‐selektive Alkinhydroacylierung in eine verzweigt(b)‐selektive Reaktion „umgeschaltet“ werden (siehe Schema). Strukturdaten des o‐iPr‐dppe‐Rh‐Katalysators lassen vermuten, dass eine gehinderte Rotation um die Phosphanaryl‐Einheiten für die Selektivität verantwortlich ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…[17] Although there are now an umber of successful non-chelation intermolecular hydroacylation methods, [18,19] the most general and selective processes invariably rely on chelation control and have allowed the development of reactions that operate under mild conditions, employ low loadings of catalyst and achieve high levels of selectivity. [20] Accordingly,w eselected chelating aldehydes as our preferred substrates. The presence of coordinating functionality on the alkene or alkyne coupling partner has also been shown to have as ignificant impacto nt he course of several hydroacylation reactions, and has been employed to facilitate both reactivity and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Although there are now an umber of successful non-chelation intermolecular hydroacylation methods, [18,19] the most general and selective processes invariably rely on chelation control and have allowed the development of reactions that operate under mild conditions, employ low loadings of catalyst and achieve high levels of selectivity. [20] Accordingly,w eselected chelating aldehydes as our preferred substrates. The presence of coordinating functionality on the alkene or alkyne coupling partner has also been shown to have as ignificant impacto nt he course of several hydroacylation reactions, and has been employed to facilitate both reactivity and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…[3a,8] Wide-bite-angle,o rs terically bulky,l igands have this effect, but also change the ratio of alkene versus aldehyde hydroacylation [9] or the linear/branched selectivity. [10] Additionally,these systems in general still require high loadings,a nd activated alkenes or terminal alkynes as substrates.S mall-bite-angle phosphine ligands,R 2 PCH 2 PR 2 (e.g.,R= t Bu, Cy), initially developed by Hofmann et al, [11] have been shown to favor the products of reductive elimination [12] and we recently demonstrated that catalyst systems exemplified by [Rh(R 2 PCH 2 PR 2 )(h 6 -C 6 H 5 F)][BAr F 4 ][ R = t Bu, 1;A r F = 3,5-C 6 H 3 (CF 3 ) 2 ]c an be used at low catalyst loadings (e.g., 0.1 mol %) to couple terminal and activated internal alkenes with b-substituted aldehydes. [13] However, challenging internal alkenes are still out of reach with this system, as decarbonylation now outruns productive turnover.…”
mentioning
confidence: 99%
“…In [D 6 ]acetone the C 6 H 5 Fl igand in 3a is replaced by acetone to form [Rh(2a)(acetone) 2 ][BAr F 4 ]. [13,16] [10,13,16] Over 2.5 ht his reaction proceeded to give the corresponding decarbonylation product [Rh(2a)-(SMePh)(CO)][BAr F 4 ]( 9). This timescale for decarbonylation is similar to that for 1, [13b] suggesting that the OMe group does not offer strong stabilization to the acyl hydride in the absence of alkene.U se of the aldehyde 2-(diphenylphosphino)benzaldehyde (4b)l ed to am ore stable complex, [13b, 19] which did not decarbonylate,a nd formed as as ingle isomer [ Hydrogen atoms are not shown.…”
mentioning
confidence: 99%
“…[1,2] Orthosubstitution at phosphorus aryl-substituents is one method to do this, and there are a number of examples of how orthofunctionalization can affect the coordination geometry, [3] reactivity [4][5][6] and selectivity of homogeneous catalysts. [7][8][9][10] Ortho-fluorine substitution, however, is much rarer. [11,12] Orthoaryl fluorine substitution has been used to increase the rate of biphenyl reduction in Pt(Ph) 2 (o-F-diphosphine) complexes, [13] and shown to increase catalyst productivity in Cr-catalyzed ethylene oligomerisation.…”
Section: Introductionmentioning
confidence: 99%